Методические подходы к изучению показателей финансового состояния предприятия - Погорелов, Игорь Николаевич (НТУ "ХПИ", 2015)
В статье рассмотрены вопросы анализа финансового состояния предприятия с целью определения его неплатежеспособности. А также предложен методологический подход к планированию операционной деятельности предприятия с целью улучшения его финансового состояния. В соответствии с Методическими указаниями устанавливается степень неплатежеспособности предприятия и момент восстановления платежеспособности, изменение структуры актива баланса в сторону увеличения удельного веса оборотных активов.

On the basis of a systematic approach characterized the main form of ownership as the basic institutions of the economic system of the society, the analysis of causality between changes in the ownership relations and socio-economic situation in Ukraine over the past two and a half decades, marked urgent problems of reproduction of property relations in the process of building the state of Ukraine. It was found that the mixed ownership in the most contemporary answers to bend as globalization, the comprehensive development of man as a decisive factor of production, the task of building a modern state of Ukraine.
Methodological approaches to the study of indicators of the financial condition of the company
Keywords: финансы; прибыль; баланс; бухгалтерский учет; sphere of logistics; integrated farming